Transmisi Nilai Kritis Minangkabau: Intervensi Pendidikan Jembatan Pewarisan Adat dan Faraid Islam - Mili Sahira Saragih; Yeni Karneli; Puji Gusri Handayani (Journal of Educational Research and Learning Analytics, 2025)
This article develops a conceptual model of "Critical Integration Based on Sharia" (CIBS) grounded in Syeikh Ahmad Khotib Al-Minangkabawi's reformist thought to address the pedagogical dualism between Minangkabau customary inheritance (matrilineal) and Islamic inheritance law (Faraid). The study employs Educational Conceptual Model Design Research methodology to design a prescriptive educational intervention framework. The CIBS model integrates three foundational principles: normative principles based on Maqasid Syariah, methodological principles of culturally responsive adaptive intervention, and institutional principles emphasizing critical collaboration. The research demonstrates that Faraid, grounded in justice principles, should be presented not as antithetical to Adat but as the highest expression of genuine Minangkabau equity. Through four implementation phases conceptual definition, curriculum artifact development, capacity building, and critical evaluation the model ensures coherent value transmission across formal and non-formal institutions, particularly through Bundo Kanduang roles. This framework provides a pathway for sustainable cultural inheritance while maintaining Sharia's normative integrity, enabling younger generations to resolve internalized conflicts regarding inheritance justice within Minangkabau families.